(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2013)
Gabapentin is reported to possess antihyperalgesic and antiallodynia properties. Recently, reports have indicated that gabapentin may have a place in the treatment of postoperative pain. In this study, we sought to role of preoperative use of gabapentin on postoperative pain and pethidine consumption following laparoscopic cholecystectomy. Sixty patients of both sexes, ASA grade I and II underwent laparoscopic cholecystectomy were randomly allocated into two groups. Group A (n = 30) patients were premedicated with single dose of gabapentin (600 mg) 2 hours before operation and Group B (n = 30) with tab vitamin B complex as placebo. Operation was done under general anaesthesia. Postoperative analgesia was assessed in both groups subjectively by Visual Analogue Scale (VAS). Any patient of both groups with VAS score of more than three were administered intramuscular pethidine 1.5 mgkg-1 bodyweight for 24 hours. VAS Observations were made in postoperative ward at arrival and at 6, 12 and 24 hours for 24 hours. Total postoperative pethidine consumption and post operative side effects were also recorded. Baseline data were comparable between the two groups. The mean VAS almost similar and less than 3 at different reading in both groups and the differences were statistically not significant. The mean total cumulative amount of pethidine administered over 24 hrs period was less in group A it was 117.31+14.13mg (Mean = SD) and in group B was 221.23=16.25 mg (Mean + SD) and the difference was statistically significant (p<0.01). Incidences of side effects like PONV and urinary retention were more in group B than group A and differences were statistically significant (p<0.01). Dizziness and Somnolence were more in group A than group B and difference was statistically significant (p<0.01). Preoperative gabapentin significantly decreased postoperative opioid consumption and should be considered a potentially useful adjunctive in postoperative pain in patients undergoing laparoscopic cholecystectomy. JCMCTA 2013 ; 24 (1): 41-45